Survey paper on prototypes applied on resistance, stregth and agility tests - Fidler, Franciéli (2020)
The use of mobility, resistance and strength tests in physiotherapy treatments brings a continuous improvement of the conditions of mobility and strength of the individuals. The objective of this study is to carry out a systematic review in the literature on how these tests are performed. The used methodology is a featuring Timed Up and Go, Sit to Stand and Hand Force tests and instrumented chairs were searched in the SciELO and Pub Med databases, among others, from March to January 2019, being selected according to the inclusion or exclusion classification criteria. The results show all the articles that were chosen after the classification approach one of the three tests, or even of instrumented chairs. In all the articles it is noticed the presence of some alteration in the equipment used for the tests or even the inclusion of technologies for the same. In this work, it is concluded that the used of new technologies based on network communication is very important to improve test systems and are beneficial to the quality of results.